Pengaruh Drajat Penyosohan terhadap Mutu Fisik dan Nilai Gizi Beberapa Jenis Beras - Hasnelly Hasnelly; Evi Fitriani; Shelvi Putri Ayu; Hervelly Hervelly (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
High hulling process decreases the nutritional value and rice quality including milled rice because the macronutrient contained in the aleurone is wasted. Therefore, this study aims to ascertain the effects of hulling level on the quality and characteristics of red rice, black rice, and white rice, which would help produce high quality milled rice. Linear regression method was used, and the contents analysed were moisture, fat, ash, carbohydrate, anthocyanin, quality, rendemen, starch digestibility, and color. The results showed hulling would affect the proximate content and physical characteristics of milled rice. Also, low hulling of black rice produced the highest physical score, with high anthocyanin, and low starch digestibility which was good for diabetic consumers.